PENGARUH MOTIVASI DAN GAYA HIDUP KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN HANDPHONE ANDROID - Syahril, Romi (Universitas Bina Sarana Informatika, 2017)
This study aims to analyze the effect of motivation and lifestyle on the buying decision of android. The research was carried out in different places to get the respondents. Sample this research is the user's android, which amounts to 100 respondents. Regression analysis techniques were used to analyze the impact of motivation and lifestyle on android purchasing decisions using multiple linear regression. The analysis showed that there was a significant effect of motivation and the lifestyle on buying decision with R2 value of 0,188. This suggests that higher levels of motivation and lifestyle the consumer users will increase buying decision androidKeywords: Motivation, Lifestyle, Buying Decision